The complete chloroplast genome of ornamental and medicinal Callerya dielsiana (Fabaceae) - Qi-Fei Yi; Li-Na Han; Ming-Chen Lin; Yong Tan; Lin Fu; Lei Duan; Hong-Feng Chen (Mitochondrial DNA. Part B. Resources, 2022)
Callerya dielsiana is a Chinese endemic tropical/subtropical liana. We sequenced the complete chloroplast genome with the Illumina Hiseq X-Ten platform. The genome is obtained with 132,301 bp in length, lacking an inverted repeat (IR) region, contains 4 rRNAs, 30 tRNAs genes, and 76 protein-coding genes. The overall GC content is 33.9%. Based on the whole chloroplast genomes of 14 legume species, a phylogenetic tree is constructed and indicated that C. dielsiana belongs to the well-supported tribe Wisterieae. The tribe is sister to Glycyrrhiza and nested within the IRLC (Inverted Repeat-Lacking Clade) group of the subfamily Papilionoideae (Fabaceae).